The Influence of Road Geometric Design on Traffic Accident Rates on Jalan Mayjend Sungkono, Malang City - Palupi, Retno; Mahmud, Mahmud; Khilmi, Muhamad; Triawati, Indri; Winoto, Djarot; Wibowo, Akbar (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
Traffic safety is a critical concern on urban roads, including Jalan Mayjend Sungkono in Malang City, which experiences high accident rates. This study aims to analyze the influence of geometric road design and user behavior on traffic accidents from 2008 to 2020. Factors such as varying road widths, steep slopes, inadequate signage, and limited pedestrian facilities were identified as major contributors to traffic hazards. Additionally, risky driving behaviors and the dominance of motorcycles and private cars highlight safety challenges. The research employed a quantitative descriptive-analytical method. Primary data was collected through field surveys measuring geometric elements such as curve radius, superelevation, and grade. Secondary data on accident rates were sourced from police records. A polynomial regression analysis was conducted to determine the relationship between geometric factors and accident frequency. The coefficient of determination (R²) values for elements such as clear zones (57%), grade (50.04%), and superelevation (36%) indicated their significant impact on accident rates. Traffic patterns revealed peak hours during 6:00–9:00 AM and 4:00–7:00 PM, with weekend surges due to recreational activities. Results show that geometric improvements, particularly in clear zones and road grade, could substantially reduce accidents. Behavioral factors, such as speeding and abrupt stops by public transport, also exacerbate risks. Pedestrian safety remains a concern due to the lack of adequate crossings and sidewalks, especially near schools and markets. This study underscores the importance of integrated interventions involving road design enhancements and stricter traffic regulation enforcement to improve safety on Jalan Mayjend Sungkono.